2018
DOI: 10.3917/jie.025.0057
|View full text |Cite
|
Sign up to set email alerts
|

Patents and Open Innovation: Bad Fences Do Not Make Good Neighbors

Abstract: Distribution électronique Cairn.info pour De Boeck Supérieur. © De Boeck Supérieur. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 106 publications
0
5
0
2
Order By: Relevance
“…At the subsequent stage, patents inspire their implementation in the economy through the transfer of licences. Thus, the patents' prices grow more dynamically [8]. Studies have confirmed that external R&D partners have access to the patent's imminent knowledge resource and tacit IP knowledge.…”
Section: Related Literaturementioning
confidence: 99%
“…At the subsequent stage, patents inspire their implementation in the economy through the transfer of licences. Thus, the patents' prices grow more dynamically [8]. Studies have confirmed that external R&D partners have access to the patent's imminent knowledge resource and tacit IP knowledge.…”
Section: Related Literaturementioning
confidence: 99%
“…Since the uses of patents significantly differ across technological fields and industries (Orsenigo et al, 2010), we would also expect significant differences in the recording lags of patent transactions. In particular, since the Information and Communications Technology (ICT) sector is the most prone to notice failure (Menell and Meurer, 2013) and to opportunistic patent litigation (Bessen et al, 2008) -due to a mix of factors, like the complexity of the technology, the large number of patents filed and the fast obsolescence of the technology (Pénin and Neicu, 2018) -, we would expect longer recording lags when transactions concern ICT patents are that are acquired for litigation purposes, especially when the patent buyer is a PAE.…”
Section: Ict Sectormentioning
confidence: 99%
“…Finally, they help manage the outflows of knowledge and the distribution of profits by enabling either out-licensing strategies or by ensuring the maintenance of exclusivity and its associated profits. As such, in open innovation, firms are not only producers but also active users of patents and other means of intellectual property rights (IPRs) (Pénin and Neicu 2018).…”
Section: Open Innovation and Intellectual Propertymentioning
confidence: 99%